Large-scale online education programmes and their potential to effect change in behaviour and practice of health and social care professionals: a rapid systematic review. Issue 5 (18th August 2019) - Zubala, Ania; Lyszkiewicz, Kacper; Lee, Elaine; Underwood, Laura L.; Renfrew, Mary J.; Gray, Nicola M.
ABSTRACT: This rapid systematic review examined the reported effects of large-scale online education on the behaviour and, ultimately, practice of health and social care professionals. Electronic databases of health and education literature were searched, 193 unique records were screened against inclusion and exclusion criteria, 31 papers were accessed for full text reading and six were included. Identified studies reported primarily qualitative results, which were synthesised according to outcomes. Factors that contributed to the results were also identified. All papers reported that participation in e-learning programmes resulted in changes in behaviour and practice, including: increased awareness, changes in attitudes, improved communication, increased confidence and the actual changes applied in a workplace. Observed benefits of these programmes ranged from gaining new insights into own practice, through feeling empowered to apply changes, to eventually being able to provide more person-centred services and willing to adopt and spread a more humane evidence-based practice. While the current study is an early indication of the potential of large-scale online education to effect practice change, further research is recommended as is further in-depth investigation into how these changes are achieved and what factors contribute to success.